CLINICAL PROFILE OF STROKE SEVERITY BASED ON NIHSS, MORTALITY, AND PNEUMONIA INCIDENCE AMONG FEMALE STROKE PATIENTS - Arisetijono, Eko; Putri, Adecya Amaryllis Risa; Andarini, Sri; Agustin, Aisyiyah Alviana (MNJ (Malang Neurology Journal), 2026)
Background: Stroke is a leading cause of mortality and long-term disability worldwide, with women exhibiting distinct clinical characteristics and generally poorer outcomes than men. Female-specific risk factors, older age at onset, and greater stroke severity contribute to unfavorable prognoses. As a tertiary referral center in East Java, Dr. Saiful Anwar General Hospital treats a large number of female stroke patients, yet comprehensive clinical data remain limited. Objective: To describe the clinical profile of female stroke patients, focusing on stroke severity based on NIHSS scores, mortality, and pneumonia incidence. Methods: This retrospective descriptive study included 202 female stroke patients admitted between January and December 2024. Data were extracted from electronic medical records. Results: Most patients were aged 45–64 years (46.5%) or ≥65 years (44.6%), and the majority were housewives (80.2%). Thrombotic stroke predominated (55.4%) over intracerebral hemorrhage (44.6%). Hypertension was the most prevalent vascular risk factor (96.0%), followed by diabetes mellitus (42.1%), dyslipidemia (35.1%) and heart disease (32.2%). Stroke severity was predominantly moderate to very severe, with 91.1% of patients presenting with NIHSS scores ≥5. Pneumonia was the most frequent complication (51.5%). Overall mortality reached 45.0%. Conclusion: Female stroke patients demonstrated a high burden of vascular risk factors, severe neurological impairment, frequent complications, and mortality far exceeding global averages. These findings highlight the urgent need for strengthened prevention strategies, improved acute stroke care, early complication management, and targeted interventions for this vulnerable population.